2015
DOI: 10.1186/s12860-015-0069-1
|View full text |Cite
|
Sign up to set email alerts
|

Extended 2D myotube culture recapitulates postnatal fibre type plasticity

Abstract: BackgroundThe traditional problems of performing skeletal muscle cell cultures derived from mammalian or avian species are limited myotube differentiation, and transient myotube persistence which greatly restricts the ability of myotubes to undergo phenotypic maturation. We report here on a major technical breakthrough in the establishment of a simple and effective method of extended porcine myotube cultures (beyond 50 days) in two-dimension (2D) that recapitulates key features of postnatal fibre types.Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Maintaining such protracted cultures of various cell types, especially skeletal muscle cells, can pose challenges due to potential delamination post-differentiation and the resultant deleterious effects on cell viability. Nonetheless, numerous studies have successfully sustained viable and functional differentiated myoblasts over extended culture durations, both in 2D [52,53] and 3D [54,55] cultures. In this study, uncontrolled cell delamination was not observed, and sustained cell viability was validated through in vitro Toxicology Assay Kit at various intervals, coupled with live-dead staining at the end.…”
Section: Discussionmentioning
confidence: 99%
“…Maintaining such protracted cultures of various cell types, especially skeletal muscle cells, can pose challenges due to potential delamination post-differentiation and the resultant deleterious effects on cell viability. Nonetheless, numerous studies have successfully sustained viable and functional differentiated myoblasts over extended culture durations, both in 2D [52,53] and 3D [54,55] cultures. In this study, uncontrolled cell delamination was not observed, and sustained cell viability was validated through in vitro Toxicology Assay Kit at various intervals, coupled with live-dead staining at the end.…”
Section: Discussionmentioning
confidence: 99%
“…Because myogenin is mostly expressed during terminal stages of myogenic differentiation [ 54 , 55 ], longer cultivation periods of at least up to 28 d would be one future goal. Although cell detachment after 28 d of cultivation made it impossible to analyse the gene expression during longer observation periods so far, coating with collagen type I or Maxgel™ (consisting of an undefined composition of human extracellular matrix components) may be a possibility to overcome cell detachment in future experiments [ 56 ]. Furthermore, myogenin is known to peak at some point of myoblast differentiation and then decline to lower expression afterwards.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these results showed that highly pure SCs can be used as a cell model for the next experiment. As shown in the experiment, porcine myocytes were identified by proliferation and differentiation within 5 days with a nearly 80% differentiation fusion index manifested in an abundance of discrete MyHC [ 47 ]. We treated the myocytes with the TCMF extractions after 96 h of induction with 2% horse serum.…”
Section: Discussionmentioning
confidence: 99%